Para além da justiça formal : Hegel e o formalismo kantiano - Salvadori, Mateus (2014)
This thesis has a dual purpose: to defend Hegel's criticism of Kant s formalism and to show that, from Hegel's theory of justice, there is an overcoming of Kant s formal justice. While Kant remains attached to the formalism by the categorical imperative of duty, Hegel, through a non-formal theory of justice, points out contentful principles in order to establish particular duties from them. In addition, Kant, when dealing with the law, carries a moral justification of the legal; however, in front of the law of equity and of the law of necessity, he ends up not recognizing them as rights and claiming that the judge cannot do anything about them because both of them are doubtful rights . For Hegel, in turn, the emergency law is not merely a concession, but a fundamental right. Moreover, when dealing with the right to say no , the Constitution (non-formal, non-judgmental and non-normative) and the World Spirit (a non-formal criterion of justice), he argues that formalism is insufficient, since without contentful principles one cannot know my duty . It follows that a theory of justice must be built from the ethos of a people. State, Law, justice and freedom are the central concepts of this thesis.